Enhancement in the double Higgs boson production by e+ e− annihilation and physics beyond the standard model. - Vásquez Tocora, Andrés Felipe (2018)
The main goal of this dissertation is to show the enhancement of the cross-section for the double Higgs production through pair annihilation by including effective interactions and through the non-perturbative Sommerfeld effect. Bounds to some Wilson coefficients were obtained from such enhancement, this in the scenarios of the future e+ e− -colliders (FCC-ee, ILC, CLIC). In order to achieve this, some computational tools were implemented: FeynRules, FeynArts, FormCalc, and LoopTools. It is also shown the enhancement of the double Higgs production in 2HDM and MSSM, discussing the general framework of these two models. In addition, it is studied the threshold behavior of the cross-section for the double Higgs production when a hidden sector couples to the Higgs boson, yielding resonances below the threshold energy due to non-perturbative effects. We study the Sommerfeld effect in the double Higgs production in the scenario of e+ e− -colliders. The enhancement is discussed as generated from a hidden sector coupled to the Higgs boson. Below and above threshold enhancements are presented. Such analysis is of importance in the ILC project, which will operate up to the threshold energy √s = 250 GeV. The results has been achieved by the use of computational tools like FeynArts, FormCalc, and LoopTools.